Horizontal Gene Transfer and Tandem Duplication Shape the Unique CAZyme Complement of the Mycoparasitic Oomycetes Pythium oligandrum and Pythium periplocum - Liang, Dong; Andersen, Christian Benjamin; Vetukuri, Ramesh R.; Dou, Daolong; Grenville-Briggs, Laura J. (Frontiers in Microbiology, 2020)
Crop protection strategies that are effective but that reduce our reliance on chemical pesticides are urgently needed to meet the UN sustainable development goals for global food security.Mycoparasitic oomycetes such as Pythium oligandrum and Pythium periplocum, have potential for the biological control of plant diseases that threaten crops and have attracted much attention due to their abilities to antagonize plant pathogens and modulate plant immunity. Studies of the molecular and genetic determinants of mycoparasitism in these species have been less well developed than those of their fungal counterparts. Carbohydrate-active enzymes (CAZymes) from P. oligandrum and P. periplocum are predicted to be important components of mycoparasitism, being involved in the degradation of the cell wall of their oomycete and fungal prey species. To explore the evolution of CAZymes of these species we performed an in silico identification and comparison of the full CAZyme complement (CAZyome) of the two mycoparasitic Pythium species (P. oligandrum and P. periplocum), with seven other Pythium species, and four Phytophthora species. Twenty CAZy gene families involved in the degradation of cellulose, hemicellulose, glucan, and chitin were expanded in, or unique to, mycoparasitic Pythium species and several of these genes were expressed during mycoparasitic interactions with either oomycete or fungal prey, as revealed by RNA sequencing and quantitative qRT-PCR. Genes from three of the cellulose and chitin degrading CAZy families (namely AA9, GH5_14 and GH19) were expanded via tandem duplication and predominantly located in gene sparse regions of the genome, suggesting these enzymes are putative pathogenicity factors able to undergo rapid evolution. In addition, five of the CAZy gene families were likely to have been obtained from other microbes by horizontal gene transfer events. The mycoparasitic species are able to ultilize complex carbohydrates present in fungal cell walls, namely chitin and N-acetylglucosamine for growth, in contrast to their phytopathogenic counterparts. Nonetheless, a preference for the utilisation of simple sugars for growth appears to be a common trait within the oomycete lineage.